2020
DOI: 10.1519/jpt.0000000000000261
|View full text |Cite
|
Sign up to set email alerts
|

Section of the Balance Evaluation Systems Test (BESTest) Cutoff Values for Walking Speed Level in Older Women With Hip Fracture

Abstract: Background and Purpose: Hip fracture is a common injury in older adults, with a high proportion of hip fractures affecting women. After a hip fracture, the recovery of the patient's walking speed is very important; one of the key determinants of walking speed is balance. The Balance Evaluation Systems Test (BESTest), a clinical balance measure, categorizes balance into 6 postural control systems. However, the relationship between the walking speed level and the sections of the BESTest has not been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 44 publications
1
8
1
Order By: Relevance
“…The stability in gait section showed good accuracy in discriminating between groups, with a good combination of sensitivity and specificity, and the positive predictive value was also high. This finding was in line with previous studies that analysed walking speed in relation to BESTest or Brief-BESTest section scores in older adults ( 14 , 27 ). It is interesting that the stability in gait section is strongly related to walking speed regardless of subject characteristics.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The stability in gait section showed good accuracy in discriminating between groups, with a good combination of sensitivity and specificity, and the positive predictive value was also high. This finding was in line with previous studies that analysed walking speed in relation to BESTest or Brief-BESTest section scores in older adults ( 14 , 27 ). It is interesting that the stability in gait section is strongly related to walking speed regardless of subject characteristics.…”
Section: Discussionsupporting
confidence: 93%
“…walking): progression, postural control, and adaptation. A relationship between each of these 3 essentials of walking and specific sections of the BESTest has been suggested, with progression corresponding to biomechanical constraints; postural control corresponding to stability limits and verticality, anticipatory postural adjustments, postural response, and sensory orientation; and adaptation corresponding to anticipatory postural adjustments, postural response, and stability in gait ( 14 ). Also, the cut-off scores obtained between household ambulators or limited community ambulators in these 3 sections were low, from 36.1% to 50.0%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, we indicated the cutoff scores of 5 BESTest sections that could differentiate the walking speed of older women with hip fracture and classify them as fast or slow walkers. 28 However, for these community-dwelling older adults, no previous study has used individual sections of the BESTest or the Brief-BESTest to evaluate the balance deficits, or indicated the cutoff scores of each section related to the walking speed. The cutoff scores for discriminating walking speed are clinically useful because they can serve as targets in physical therapy to improve walking speed or prevent a decline in walking speed for community-dwelling older adults.…”
Section: Research Reportmentioning
confidence: 99%
“…Therefore, the selection of the balance assessment scale is important for appropriate evaluation and intervention in the subject. It is desirable to be able to translate the results of the assessment into interventions that have been reported in recent years (11,12).…”
Section: Response To Letter To the Editor From Franco Franchignoni Anmentioning
confidence: 99%